An Enhanced House Price Index Model in Malaysia: A Laspeyres Approach - Nik Mohd Sukrri, Nik Amalina; Abd. Wahab, Norazlina; Mohd Yusof, Rosylin (Kulliyyah of Economics and Management Sciences, International Islamic University, Malaysia, 2019)
The purpose of this study is to develop an enhanced house price index model in Malaysia. At the same time, it attempts to examine the determinants of the existinghouse price index in Malaysia. Review of thecurrent Malaysian House Price Index (MHPI) model shows that this index is constructed based on demand driven variables. Past studies explained that both macroeconomic factors (income levels, interest rates, labor market) and supply factors are included in constructing the house price index. Therefore, this study aims at providing evidence on the determinants of the House Price Index (HPI). This study employs the Autoregressive Distributed Lag Model (ARDL) to discover the short and long-run dynamics between the variables. The study considers the quarterly data from first quarter 2008 to fourth quarter 2015. The analysis shows that supply and institutional factors are significant in determining the HPI. Hence, we propose anew enhanced house price index incorporating new demand and supply variables. By using LaspeyresApproach, the new enhanced HPI has been calculated. The findings revealed that MHPI was found to have a long run significant relationship with employment, Overnight Policy Rate (OPR), Consumer Price Index (CPI), land supply and housing loan while construction cost is not significant in determining the MHPI